Recent advances in overcoming barriers to cell‐based delivery systems for cancer immunotherapy - Yingyue Ding; Yixin Wang; Quanyin Hu (Exploration, 2022)
Abstract Immunotherapy strategies that use cell‐based delivery systems have sparked much interest in the treatment of malignancies, owing to their high biocompatibility, excellent tumor targeting capability, and unique biofunctionalities in the tumor growth process. A variety of design principles for cell‐based immunotherapy, including cell surface decoration, cell membrane coating, cell encapsulation, genetically engineered cell, and cell‐derived exosomes, give cancer immunotherapy great potential to improve therapeutic efficacy and reduce adverse effects. However, the treatment efficacy of cell‐based delivery methods for immunotherapy is still limited, and practical uses are hampered due to complex physiological and immunological obstacles, such as physical barriers to immune infiltration, immunosuppressive tumor microenvironment, upregulation of immunosuppressive pathways, and metabolic restriction. In this review, we present an overview of the design principles of cell‐based delivery systems in cancer immunotherapy to maximize the therapeutic impact, along with anatomical, metabolic, and immunological impediments in using cell‐based immunotherapy to treat cancer. Following that, a summary of novel delivery strategies that have been created to overcome these obstacles to cell‐based immunotherapeutic delivery systems is provided. Also, the obstacles and prospects of next‐step development of cell‐based delivery systems for cancer immunotherapy are concluded in the end.